Strategi Meningkatkan Kualitas Pelayanan Pramusaji: Studi di Restoran Mozzarella By The Sea The Bandha Hotel & Suites Legian Bali - Ni Made Anggita Pratiwi; Ni Nyoman Rusmiati; Pondang Polikarpus Nainggolan (CV Global Research Publication, 2026)
This study aims to examine management efforts to improve the quality of waitstaff service, identify the challenges faced, and analyze the solutions implemented at Mozzarella By The Sea Restaurant, The Bandha Hotel & Suites Legian, Bali. The study employs a qualitative descriptive approach, utilizing data collection techniques such as observation, interviews, and documentation. A total of six research informants were selected through purposive sampling, consisting of the Assistant Food and Beverage Manager and the Restaurant Manager as key informants, as well as waiters/waitresses and daily workers as supporting informants. The results of the study indicate that management has implemented various efforts to improve the quality of waitstaff service through daily and monthly briefings, product knowledge training, and the implementation of Standard Operating Procedures (SOPs) such as repeat orders. Additionally, management provides training on personal grooming to enhance the professionalism of the waitstaff. However, several challenges exist, such as low waitstaff awareness regarding attendance at briefings, limited retention of training materials, and individual skill disparities, which continue to result in service errors. To address these challenges, management has implemented personal evaluations, repeated training content during briefings, and work schedules tailored to waitstaff capabilities. These efforts are deemed sufficiently effective in improving service quality, although consistent implementation remains necessary.